1992
DOI: 10.1520/jfs13358j
|View full text |Cite
|
Sign up to set email alerts
|

Surface Contamination by TNT

Abstract: We have performed experiments that indicate TNT contamination is present on surfaces exposed to TNT vapor, and that TNT contamination is transferred rapidly between proximate surfaces. Contaminated surfaces continue to be nearly constant sources of TNT vapor for some time after removal of the primary source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…(16) Although its vapor pressure is very low at room temperature, TNT has been shown to contaminate surfaces (such as wood, rubber, aluminum) placed near but not touching the TNT. (17) In the case of porous materials such as wood, significant TNT contamination was found not only on the surface but also throughout the wood. (17) This tendency of explosive materials to spread can be an advantage for forensic investigations and for efforts to prevent terrorist activities.…”
Section: Solid Sample Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…(16) Although its vapor pressure is very low at room temperature, TNT has been shown to contaminate surfaces (such as wood, rubber, aluminum) placed near but not touching the TNT. (17) In the case of porous materials such as wood, significant TNT contamination was found not only on the surface but also throughout the wood. (17) This tendency of explosive materials to spread can be an advantage for forensic investigations and for efforts to prevent terrorist activities.…”
Section: Solid Sample Mixturesmentioning
confidence: 99%
“…(17) In the case of porous materials such as wood, significant TNT contamination was found not only on the surface but also throughout the wood. (17) This tendency of explosive materials to spread can be an advantage for forensic investigations and for efforts to prevent terrorist activities. However, it also implies that great care must be taken to ensure that any explosive material detected is from the sample of interest and not from previous contaminated samples (memory effects), from other samples stored in the laboratory, or from handling of the sample.…”
Section: Solid Sample Mixturesmentioning
confidence: 99%
“…These same vapors are also emitted by intact mines ) and contaminate their surfaces (Leggett et al 2000). Vapor-contaminated materials, themselves, remain a source of vapors for many days (Bender et al 1992). These emitted vapors are sorbed and concentrated on soil around buried landmines (George et al 1999).…”
Section: Tablesmentioning
confidence: 99%
“…In addition, highly confined explosives are likely to emit only small amounts of vapor into their surroundings. Furthermore, it has been shown that vapors emanating from several nitroaromatic explosives tend to adsorb onto surrounding surfaces rather than undergo mass transport [3,4]. For these reasons, high detection sensitivity is critical.…”
Section: Introductionmentioning
confidence: 99%